A Multicenter Randomized Double-Masked Study Comparing Preservative-free Brimonidine Tartrate Ophthalmic Solution 0.025% with LUMIFY® 0.025% for Ocular Redness in Adults - Melissa Toyos; Melinda DiVito; Elisabeth M. Messmer; Selina McGee; Jared Peterson; Assem Patel; Guruprasad Pattar; David G. Evans; Patrick M. Vollmer; Gina Wesley (Ophthalmology and Therapy)
Abstract Introduction Ocular redness is common, can affect quality of life, and can be relieved by short-term use of topical adrenergic receptor (AR) agonists. Brimonidine tartrate ophthalmic solution 0.025% (LUMIFY® 0.025%) is the first α2-AR-selective agonist approved for ocular redness. The preservative benzalkonium chloride (BAK) maintains ophthalmic solution sterility, reducing the risk of ocular infections, but may cause symptoms of ocular surface disease (OSD) in some patients. A BAK-free formulation of LUMIFY 0.025% (BTOS-PF 0.025%) could offer a solution for BAK-sensitive patients. Methods This randomized, active-controlled, multicenter study aimed to establish non-inferior efficacy of BTOS-PF 0.025% to LUMIFY 0.025% and compare safety. Randomized participants received either formulation instilled as a single drop four times daily, for 4 weeks. The primary endpoint was investigator-assessed ocular redness at 5, 15, 30, 60, 90, 120, 180, and 240 min post-instillation at visit 1 (day 1). Eight hierarchical secondary endpoints included additional post-instillation timepoints at visit 1 and visits 2 and 3 (days 14 and 28), and participant-assessed redness. Results BTOS-PF 0.025% was statistically non-inferior to LUMIFY 0.025% for ocular redness reduction across the eight timepoints at visit 1. Efficacy for both formulations was seen as early as 1 min and up to 8 h post-instillation. BTOS-PF 0.025% performed similarly to LUMIFY 0.025% after 14 and 28 days, rebound redness rates were low and similar, and total clearance of ocular redness and participant-evaluated redness were similar. The safety profile of both formulations was similar, with no severe or serious ocular events. Conclusions BTOS-PF 0.025% was non-inferior to LUMIFY 0.025% in reducing ocular redness in adults, was well-tolerated, and offers an alternative topical solution, without loss of efficacy or compromised safety, for patients who prefer a preservative-free formulation or are at increased risk of OSD. Clinical Trial Registration ClinicalTrials.gov identifier: NCT05360784. Date of registration: 29 April 2022.